2011
DOI: 10.1109/tbcas.2010.2095847
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characteristics of a Multichannel Front-End ASIC Using Current-Mode CSA for Small-Animal PET Imaging

Abstract: This paper presents the design and characteristics of a front-end readout application-specific integrated circuit (ASIC) dedicated to a multichannel-plate photodetector coupled to LYSO scintillating crystals. In our configuration, the crystals are oriented in the axial direction readout on both sides by individual photodetector channels allowing the spatial resolution and the detection efficiency to be independent of each other. Both energy signals and timing triggers from the photodetectors are required to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 21 publications
0
21
1
Order By: Relevance
“…9. It is indicated that the proposed scheme can achieve better nonlinearity performances than that of the traditional method which samples the energy voltage by using an analog memory and a monostable circuit [5]. The nonlinearity of the traditional peak-detect-and-hold method versus the proposed data acquisition scheme.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…9. It is indicated that the proposed scheme can achieve better nonlinearity performances than that of the traditional method which samples the energy voltage by using an analog memory and a monostable circuit [5]. The nonlinearity of the traditional peak-detect-and-hold method versus the proposed data acquisition scheme.…”
Section: Resultsmentioning
confidence: 98%
“…The peak value of the shaped voltages are sampled by a peak-detect-and-hold circuit [5]. The triggers are achieved by a high-speed high-resolution discriminator.…”
Section: Introductionmentioning
confidence: 99%
“…A number of integrated circuits with the number of channels up to 128 have been developed for readout and processing signals of SiPM cells and arrays [18][19][20][21][22][23][24][25][26][27][28][29]. Most of them are designed for application in medical scanners, and multi-channel detectors of physical installations.…”
Section: Introductionmentioning
confidence: 99%
“…This emitted positron upon combining with nearby electron produces two back-to-back photon of 511KeV energy. This photon pair is detected by scintillator and APD [1]- [6]/PMT [7]- [8] based detector module. For APD based detector module [1] the signal is processed by charge sensitive amplifier (CSA), pulse shaper, discriminator, peak detector and hold circuit.…”
Section: Introductionmentioning
confidence: 99%